Evaluation of Antibiotic Use in Pediatric Patients Hospitalized with Acute Diarrhea as a Result of Clinical Pathway Implementation in Hospital - Norman Dyanto; Diana Laila Ramatillah; Baharudin Ibrahim (Eduvest - Journal of Universal Studies, 2024)
This study aims to determine the effectiveness of clinical pathway implementation in pediatric patients with acute diarrhea with mild-moderate dehydration on clinical outcomes, length of stay, use of quality and quantity of antibiotics at North Jakarta Teaching Hospital. This study is a quantitative study using a retrospective cohort case study method. The samples in this study were pediatric patients with a diagnosis of acute diarrhea with mild-moderate dehydration who were hospitalized at the North Jakarta Teaching Hospital for the period January-December 2020 and JanuaryDecember 2021 before and after the implementation of the clinical pathway, totaling 274 patients. The data used is secondary data in the form of medical records of pediatric patients with acute diarrhea with mild-moderate dehydration who were hospitalized at the North Jakarta Teaching Hospital. The data that has been collected is then processed and analyzed using the chi-square test. The results showed Qualitative use of antibiotics with the Gyssens method after the application of clinical pathway is better than before the application of clinical pathway. Quantitative antibiotic administration with the DDD method in pediatric patients with acute diarrhea with dehydration before and after the application of clinical pathway the highest was ceftriaxone antibiotics after the application of clinical pathway with DDD/100 patient-days value increased compared to before clinical pathway.